Peningkatan Pemahaman Konsep Matematika Melalui Model Pembelajaran Think Pair Share Berbantuan Mystery Box - Joko Suprayitno, Iswahyudi; Prihaswati, Martyana; Umaroh, Anisa (Cartesian: Jurnal Pendidikan Matematika, 2026)
Inadequate understanding of mathematical concepts among students remains a significant problem, largely due to the use of methods that focus on memorization rather than understanding, which leads to student passivity. This study aims to analyze the improvement of students' understanding of mathematical concepts through the application of the Think Pair Share approach facilitated by the Mystery Box on the topic of flat-sided geometric shapes. This study used a quasi-experimental methodology using a Nonequivalent Control Group Design. The study sample included 8th-grade students, with 35 participants in the experimental group and 37 participants in the control group. The research instrument used a conceptual understanding assessment consisting of pretest and posttest questions. The findings indicate substantial differences in conceptual knowledge between the experimental and control classes. The improvement of conceptual understanding skills in classes using the Think Pair Share model equipped with the Mystery Box was superior to that in classes using traditional learning methods. The N-Gain achievement indicates that the success rate of using the model and media is in the moderate range. The application of the Think Pair Share approach combined with the Mystery Box improves students' understanding of mathematical concepts related to flat-sided geometric shapes.